Analysis of high-mountain vegetation of the Kurai Ridge - Popova Ekaterina (EDP Sciences, 2021)
The paper presents a taxonomic, areographic and belt-andzonal analysis of the high-mountain flora of the Kurai Ridge. The flora of the region in question contains 312 species of plants, referred to 143 genera belonging to 48 families. Analysis of the taxonomic structure of the high-mountain flora of the Kurai Ridge has shown the following most abundant plant families: Asteraceae, Ranunculaceae, and Poaceae. For the variety of the genera, the following genera are predominant: Carex, Pedicularis, Salix, and Oxytropis. The areographic analysis has demonstrated that the said species are of the North Asian (21 %), South Siberian (19.4 %) and Holarctic (17.4 %) origins. Dominant in the belt-and-zonal range are the following species: high-mountain (23.2 %), light-coniferous forest (17.7 %) and Arctic Alpine (17.4 %) species. In general, the composition and structure of the high-mountain flora of the Kurai Ridge are determined by its geographic position at the boundary of Central and South-Eastern Altai and by decrease in the amount of precipitation in the south-eastern direction.